Bearded capuchin monkeys use joint synergies to stabilize the hammer trajectory while cracking nuts in bipedal stance - Mangalam, Madhur (Proc Biol Sci, 2018)
The transition from occasional to obligate bipedalism is a milestone in human evolution. However, because the fossil record is fragmentary and reconstructing behaviour from fossils is difficult, changes in the motor control strategies that accompanied this transition remain unknown. Quadrupedal primates that adopt a bipedal stance while using percussive tools provide a unique reference point to clarify one aspect of this transition, which is maintaining bipedal stance while handling massive objects. We found that while cracking nuts using massive stone hammers, wild bearded capuchin monkeys (Sapajus libidinosus) produce hammer trajectories with highly repeatable spatial profiles. Using an uncontrolled manifold analysis, we show that the monkeys used strong joint synergies to stabilize the hammer trajectory while lifting and lowering heavy hammers. The monkeys stringently controlled the motion of the foot. They controlled the motion of the lower arm and hand rather loosely, showing a greater variability across strikes. Overall, our findings indicate that while standing bipedally to lift and lower massive hammers, an arboreal quadrupedal primate must control motion in the joints of the lower body more stringently than motion in the joints of the upper body. Similar changes in the structure of motor variability required to accomplish this goal could have accompanied the evolutionary transition from occasional to obligate bipedalism in ancestral hominins.